Effectiveness of pre-emergence herbicide imazethapyr and post-emergence herbicide fenoxaprop-p-ethyl on weed management and flower yield in marigold (Tagetes erecta L.) - AZ, Abdul Rizal; Kamalia, Aida Femnin; Arbiwati, Dyah; EK, Siwi Hardiastuti (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to determine the optimal dosage of a pre-emergence herbicide containing imazethapyr and a post-emergence herbicide containing fenoxaprop-p-ethyl for effective weed control, as well as to evaluate their impact on the yield and flower quality of marigold plants. This research was conducted in Wukirsari Village, Cangkringan District, Sleman Regency, Yogyakarta, located at coordinates 7°38’01" S – 7°40’20" S and 110°25’58"E – 110°27’54"E. The site is situated at an altitude of approximately 500 meters above sea level. The study was carried out from June to September 2024. The study was conducted using a Randomized Complete Block Design with a single factor consisting of 10 treatment levels. The treatments were as follows: (H1) imazethapyr at 0.15 kilograms a.i/ha, (H2) imazethapyr at 0.20 kilograms a.i/ha, (H3) fenoxaprop-p-ethyl at 0.10 kilograms a.i/ha, (H4) fenoxaprop-p-ethyl at 0.20 kilograms a.i/ha, (H5) imazethapyr 0.15 kilograms a.i/ha + fenoxaprop-p-ethyl 0.10 kilograms a.i/ha, (H6) imazethapyr 0.15 kilograms a.i/ha + fenoxaprop-p-ethyl 0.20 kilograms a.i/ha, (H7) imazethapyr 0.20 kilograms a.i/ha + fenoxaprop-p-ethyl 0.10 kilograms a.i/ha, (H8) imazethapyr 0.20 kilograms a.i/ha + fenoxaprop-p-ethyl 0.20 kilograms a.i/ha, (H9) mechanical weed control, and (H10) untreated (no weed control). The collected data were analyzed using Analysis of Variance at a 5% significance level. The application of Imazethapyr herbicide at a dose of 0.20 kilograms a.i/ha in combination with Fenoxaprop-p-ethyl at doses of 0.10 kilograms a.i/ha and 0.20 kilograms a.i/ha, as well as mechanical weed control, demonstrated the most effective results in suppressing weed growth in marigold cultivation. All three treatments achieved a weed control efficiency of 100%, which is classified as highly effective. These treatments also resulted in the best overall performance of marigold plants. This was reflected in the highest values recorded for flower diameter, flowering time, number of flowers per plant, total flower weight per plant, flower color intensity, and the longest vase life.